1998
DOI: 10.1038/sj.gt.3300565
|View full text |Cite
|
Sign up to set email alerts
|

Leptin gene therapy and daily protein administration: a comparative study in the ob/ob mouse

Abstract: We have compared the efficacy of daily injection of recomgiven as mean ± standard error of the mean.) Importantly, binant leptin protein (rh-leptin) with adenovirus-mediated rh-leptin and ex vivo-expressed Ad-leptin were equivalently delivery of the murine or human leptin gene (Ad-leptin) for active in a functional cell-based assay. The primary differtreatment of obesity in the obese (ob/ob) mouse model. ence in the two therapeutic approaches is the continuous We demonstrate an improved correction profile for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 8 publications
0
37
0
Order By: Relevance
“…Construction of Ad-leptin and Ad-␤-galalactosidase (␤-gal) recombinant vectors has been described (30). The expression cassettes contain the human cytomegalovirus (HCMV) promoter (Invitrogen), the transgene, and the bovine growth hormone poly(A) sequence.…”
Section: Construction Of Vectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Construction of Ad-leptin and Ad-␤-galalactosidase (␤-gal) recombinant vectors has been described (30). The expression cassettes contain the human cytomegalovirus (HCMV) promoter (Invitrogen), the transgene, and the bovine growth hormone poly(A) sequence.…”
Section: Construction Of Vectorsmentioning
confidence: 99%
“…For Northern blot analysis, total RNA was extracted (Trizol, GIBCO) from livers of Ad-leptin-treated and HD-leptin-treated mice at 1-, 2-, 4-, and 8-week intervals, and untreated mice. Leptin RNA message was detected by Northern blot analysis (35) using leptin cDNA as a probe that recognizes a single Ϸ500 bp band (30). A probe for ␤-actin was used as the internal control (Ϸ1 kb) (Biochain, San Leandro, CA).…”
Section: Construction Of Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, treatment of these animals with a recombinant adenovirus expressing the mouse leptin cDNA (AdRSV-leptin) resulted in a rapid reduction in food consumption and drastic weight loss, which led to a complete, although transient, correction of obesity and diabetes as serum leptin levels decreased after 2-3 weeks (Muzzin et al 1996). Comparing the efficacy of daily injection of recombinant leptin protein with adenovirusmediated delivery of leptin for obesity treatment, Morsy et al (1998b) found that there is a continuous chronic secretion of leptin mediated by gene delivery v. the intermittent bolus delivery and rapid clearance of the daily leptin protein injection. Furthermore, in vivo studies suggest that leptin effects are better achieved at the lower steady-state levels achieved by gene therapy.…”
Section: Gene Transfer Strategies In Obesity Modelsmentioning
confidence: 99%
“…1 Leptin gene delivery is substantially more effective in correcting genetic obesity than daily leptin infusion, despite higher peak serum leptin levels with the latter. 2 Peripheral administration of virally encoded leptin requires that the leptin crosses the blood-brain barrier (BBB) to reach its primary hypothalamic targets, but this transport system is saturated at serum leptin levels seen in obese animals. 3 Since several obese, leptin-resistant models respond better to central versus peripheral administration of recombinant leptin, [4][5][6] it has been reasoned that central delivery of the leptin gene would be superior to peripheral delivery.…”
Section: Introductionmentioning
confidence: 99%